PENYULUHAN PENGENALAN KONSELING KRISIS OLEH ORANGTUA BAGI PEMBENTUKAN PSIKOLOGI REMAJA - Marito Siringo-ringo; Lertin Zai; Lidia Kando; Rona Sulastri Hutagalung (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Crisis counseling takes place in an atmosphere of direct face-to-face communication or communication between the counselor and the adolescent which discusses various problems in individual counseling that is holistic and in-depth and touches on important things about the teenager, but is also specific towards problem solving. Through individual counseling, adolescents will understand their own condition, their environment, the problems they are experiencing, their strengths and weaknesses, and the possibility of efforts to overcome their problems. Counseling is one of the guidance techniques. Through this method efforts to provide assistance are given individually and directly face to face (communicating) between the counselor (counselor) and the client. In other words, the provision of assistance is carried out through a face-to-face relationship (four-eye relationship), which is carried out by interviewing the counselor (counselor) with the client. The problems that are solved through counseling techniques, are problems that are personal. The method used is lectures and discussions on the introduction of crisis counseling by parents for the formation of adolescent psychology. All stages have been carried out properly supported by the high participation of parents and youth.